2013
DOI: 10.1093/ndt/gft331
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and body fat distribution as renal risk factors: a focus on the role of renal haemodynamics

Abstract: Weight excess and/or central body fat distribution are associated with increased long-term renal risk, not only in subjects with renal disease or renal transplant recipients, but also in the general population. As the prevalence of weight excess is rising worldwide, this may become a main renal risk factor on a population basis, even more so because the risk extends to the overweight range. Understanding the mechanisms of this detrimental effect of weight excess on the kidneys is needed in order to design prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 46 publications
(65 reference statements)
2
45
1
1
Order By: Relevance
“…A large longitudinal study by Park et al of 43,503 Korean health screening participants found that a RHF definition based on eGFR was associated with all-cause mortality, even when adjusted for age, sex, muscle mass, diabetes and hypertension [16]. Although several studies have been conducted on the relationship between obesity and RHF [1725], it remains unclear whether these two conditions are also associated in the general non-diabetic population. The most important reason has been that there is currently no consensus on the definition of the term “hyperfiltration”.…”
Section: Introductionmentioning
confidence: 99%
“…A large longitudinal study by Park et al of 43,503 Korean health screening participants found that a RHF definition based on eGFR was associated with all-cause mortality, even when adjusted for age, sex, muscle mass, diabetes and hypertension [16]. Although several studies have been conducted on the relationship between obesity and RHF [1725], it remains unclear whether these two conditions are also associated in the general non-diabetic population. The most important reason has been that there is currently no consensus on the definition of the term “hyperfiltration”.…”
Section: Introductionmentioning
confidence: 99%
“…Augmented tubulo-glomerular feedback, proximal tubular Na resorption, increased plasma volume secondary to salt retention and systemic hypertension are hallmark features in obese patients, similar to that observed in diabetes [82]. Furthermore, recent evidence showed that a central body fat distribution is also associated with an increased filtration fraction, even independent of overall weight excess [83]. Insulin resistance causes an imbalance between afferent and efferent arterial vasomotor activity, increasing transcapillary pressure gradient causing glomerular HF.…”
Section: Association Of Hf With Obesity/metabolic Syndrome and Vasculmentioning
confidence: 74%
“…Por ello se realizó una BpR. Ella confirmó la sospecha clínica de EMBD (Figura 1) y mostró glomérulos hipertróficos compatibles con hiperfiltración glomerular, situación frecuente de observar en sujetos con resistencia a la insulina o gran masa corporal (desproporción entre masa corporal/masa renal) 13,14 . También, la ultraestructura mostró fusión pedicelar muy extensa, lo que explica la magnitud de la proteinuria.…”
Section: X)unclassified